2016
DOI: 10.5194/isprs-archives-xli-b5-675-2016
|View full text |Cite
|
Sign up to set email alerts
|

3d Digitization of an Heritage Masterpiece - A Critical Analysis on Quality Assessment

Abstract: ABSTRACT:Despite being perceived as interchangeable when properly applied, close-range photogrammetry and range imaging have both their pros and limitations that can be overcome using suitable procedures. Even if the two techniques have been frequently cross-compared, critical analysis discussing all sub-phases of a complex digitization project are quite rare. Comparisons taking into account the digitization of a cultural masterpiece, such as the Etruscan Sarcophagus of the Spouses (Figure 1) discussed in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 16 publications
0
14
0
2
Order By: Relevance
“…To resolve the problem, the authors proposed to project a known (Hafeez et al, 2017(Hafeez et al, , 2020Menna et al, 2017), random (Hosseininaveh et al, 2015;Ahmadabadian et al, 2017Ahmadabadian et al, , 2019 or synthetic (Hafeez et al, 2018(Hafeez et al, , 2020Santo si et al, 2019) pattern onto the object. Menna et al (2016) created an automated workflow based on pattern projection for 3D digitisation of heritage artifacts: various known random patterns are used to enhance dense image-matching. Ahmadabadian et al (2019) developed a lowcost and simple 3D modeling system that works by projecting a dense, random noisy pattern onto textureless Lambertian surfaces.…”
Section: Related Workmentioning
confidence: 99%
“…To resolve the problem, the authors proposed to project a known (Hafeez et al, 2017(Hafeez et al, , 2020Menna et al, 2017), random (Hosseininaveh et al, 2015;Ahmadabadian et al, 2017Ahmadabadian et al, , 2019 or synthetic (Hafeez et al, 2018(Hafeez et al, , 2020Santo si et al, 2019) pattern onto the object. Menna et al (2016) created an automated workflow based on pattern projection for 3D digitisation of heritage artifacts: various known random patterns are used to enhance dense image-matching. Ahmadabadian et al (2019) developed a lowcost and simple 3D modeling system that works by projecting a dense, random noisy pattern onto textureless Lambertian surfaces.…”
Section: Related Workmentioning
confidence: 99%
“…When massively digitising museums' artefacts for conservation, preservation, restoration, visualisation and dissemination purposes, three main requirements are generally to be satisfied: • a faithful, complete and precise reconstruction of the object's shape and geometry, limiting occlusions and avoiding loss of information; • a high-resolution and truthful texture for optimised (lowpoly) geometries, to virtually inspect in web-based and/or augmented/virtual reality applications (AR/VR); • a limited acquisition and processing time per object to perform massive digitisation activities. Both range and image-based techniques (Cignoni and Scopigno, 2008;Remondino et al, 2013;Gonizzi-Barsanti et al, 2014;Guidi et al, 2015;Russo et al, 2015;Roncella et al, 2021) demonstrated to fulfil the first need, although passive methods are preferable for the second requirement (Gattet et al, 2015;Menna et al, 2016;Menna et al, 2017;Collins et al, 2019;De Paolis et al, 2020;Rodríguez-Martín and Rodríguez-Gonzálvez, 2020;Apollonio et al, 2021;Roncella et al, 2021). However, some phases of the photogrammetric workflow can be critical in massive 3D digitisation, and a few tricks can be helpful to limit digitisation times and improve the quality of the results.…”
Section: Related Workmentioning
confidence: 99%
“…Se trata de una aplicación de código abierto diseñada para administrar y comparar nubes de puntos de alta densidad y superficies de mallas. En la documentación geométrica del patrimonio, su cálculo de la desviación promedio entre dos modelos 3D se emplea con frecuencia como herramienta para el control de calidad de los registros (Rahaman & Champion, 2019;Gagliolo et al, 2018;Grifoni et al, 2018;Menna et al, 2016). Este tratamiento de la información también ofrece un gran potencial analítico dentro del campo de la conservación, ya que permite monitorizar cambios formales.…”
Section: Análisis De Cambios Morfológicosunclassified